PERAN TRANSPORTASI DALAM MENDUKUNG KAWASAN STRATEGIS PARIWISATA NASIONAL DANAU TOBA - Budi Sitorus; Christina Natalia Sitorus (Institut Transportasi dan Logistik Trisakti, 2017)
The research objective is to identify and analyze the development problems of Lake Toba regional and support the accelerated development. The results are on the development of tourism region of Lake Toba of which improve accessibility and connectivity of transport from / to the tourist locations around the area of Lake Toba to build toll roads Kualanamu- Parapat, Silangit-Parapat and feeder roads as well as liaison adequate and smooth traffic, safe, congratulations. This research is Qualitative descriptive using a qualitative analysis approach and public policy analysis to find the steps of developing national tourism strategic areas.